Pentingnya pola asuh ibu terhadap asupan energi dan protein pada balita dengan pendapatan keluarga rendah - Dessy Putri Pratiwi; Linda Dewanti (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2020)
The importance of maternal parenting to energy and protein intake in children in a low-income familyBackground: Energy and protein insufficiency was still a major problem for Indonesian children, especially for those who live in rural areas. Objective: This study aimed to find the important role of mothers on their children's intakes in low-income families in the village of Tasikmalaya, West Java. Methods: The study was an observational research with a cross-sectional design. 120 children (6 months to 5 years old) were randomly selected from the list of children in the area. Children's intake was measured using a 2x24 hour food recall questionnaire and food frequency questionnaire (FFQ). Data were analyzed using correlation test (Spearman rho), and multiple linear regression test significance was set at p-value <0,005. Results: The majority of the children (83.3%) consumed less than four types of food (staple foods, side dishes, vegetables, and fruits), 58.3% ate the main menu <3 times/day, 13.3% of the children had low energy intake, and 7.5% had low protein intake. Although a majority of the children had normal nutritional status, 5.8% were categorized as wasting, and 2.5% overweight. There was a positive correlation between frequency of eating with energy and protein intakes of children (p=0.006; p=0.035). Types of food did not correlate to the energy and protein intakes of the children. Mother's education, children's age, and history of illness are factors that influence the energy and protein intake of the children. Conclusions: Maternal parenting (frequency of eating) correlated to the energy and protein intake of the children.